Image of the Eulogized in Al-Zubairi’s Paganisms - Radman, Ali AbdulRrab (Journal of Humanities & Social Sciences, 2019)
This research paper aimed at studying Al-Zubairi’s eulogies for Prince Ahmed (Saif-ul-Islam), the crown prince of Imam Yahiya bin Hameed Addin) before the revolution. To achieve this objective, the researcher followed a rhetorical descriptive method in order to track the image that was exaggeratedly eulogized by the poet using the eulogy purpose. The study revealed a number of results. The poet used a top-down style of eulogy whereby he moved his eulogized prince to the intended goal. He also uncovered the falsehood of what the eulogized claims, which is covered up with religion and the honor of belonging to the household of the Messenger of Allah (peace be upon him), while exercising injustice and deification. Considering these two features, the people were obliged to show all that supplication during a period of time which was not documented by anyone except Al-Zubairi through his eulogies. It was also found out that the poet did not pay heed to the consequences, but maintained the status of his poetry and eulogies by re-shifting impact into the unacceptability of the eulogized. That is so because eulogy was the only available means of expression before the ruler. Therefore, the poet presented symbolic eulogy in a way he wanted, and was understood by the ruler- and beyond that- to satisfy the people, which is all presented a symbolic type of satire. Furthermore, the study revealed that the poet did also repeat the metaphorical and simile images, and revolved them between the eulogized, poetry and the poet himself. In conclusion, when this style did not succeed the poet abandoned it and gave the name “paganisms” to his poems.